Tangeretin offers neuroprotection against colchicine-induced memory impairment in Wistar rats by modulating the antioxidant milieu, inflammatory mediators and oxidative stress in the brain tissue - Olalekan Bukunmi Ogunro; Mojisola Esther Karigidi; Gideon Ampoma Gyebi; Areej Turkistani; Ahmad H. Almehmadi (BMC Complementary Medicine and Therapies)
Abstract Background Tangeretin, a flavone compound (O-polymethoxylated) naturally present in tangerine and other citrus peels has demonstrated effectiveness as an anti-inflammatory and neuroprotective agent in several disease model. This study evaluated the impact of tangeretin in mitigating cognitive dysfunction and oxidative stress induced by colchicine in rats, comparing its efficacy with donepezil hydrochloride. Methods Cognitive dysfunction was induced by administering colchicine (15 µg/rat) intracerebroventricularly (ICV) via a stereotaxic apparatus in male Wistar rats. Colchicine resulted in poor memory retention in acquiring and retaining a spatial navigation task, passive avoidance apparatus, and Morris water maze paradigms. Chronic treatment with tangeretin (at doses of 50, 100, and 200 mg/kg, p.o. once daily) and donepezil hydrochloride (at a dose of 10 mg/kg, p.o. daily) for 28 days, starting seven days before colchicine injection, significantly ameliorated colchicine-induced cognitive impairment. Results The biochemical analysis showed that chronic administration of tangeretin effectively reversed the colchicine-induced increase in the level/activity of lipid peroxidation, hydrogen peroxide (H2O2), myeloperoxidase (MPO), nitrite, reactive oxygen species (ROS), tumour necrosis factor-α (TNF-α), nuclear factor kappa B (NF-κB), interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-10 (IL-10), serotonin, dopamine, glutamate, amyloid beta (Aβ) peptide, and caspase-3. Tangeretin also reversed the colchicine-induced reduction in the level/activity of brain-derived neurotrophic factor (BDNF), amma-aminobutyric acid (GABA), acetylcholinesterase (AChE), glutathione S-Transferase (GST), glutathione peroxidase (GPx), glutathione reductase (GR), catalase (CAT), superoxide dismutase (SOD), reduced glutathione (GSH), and total thiol (T-SH) in rat brains. However, donepezil hydrochloride did not prevent oxidative stress. Conclusions These findings suggest that chronic administration of tangeretin at 50, 100, and 200 mg/kg, p.o. once daily, was protective in mitigating colchicine-induced cognitive impairment and associated oxidative stress. At the same time, donepezil hydrochloride did not demonstrate similar effects.